2010
DOI: 10.1519/jsc.0b013e3181d7552a
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Weekly Training Load in Elite Male Professional Basketball Players

Abstract: The aim of this study was to examine the training load (TL) profile of professional elite level basketball players during the crucial parts of the competitive season (pre-play-off finals). Subjects were 8 full-time professional basketball players (age 28 +/- 3.6 years, height 199 +/-7.2 cm, body mass 102 +/- 11.5 kg, and body fat 10.4 +/- 1.5%) whose heart rate (HR) was recorded during each training session and their individual response to TL monitored using the session-rate of perceived exertion (RPE) method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
199
5
50

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 255 publications
(279 citation statements)
references
References 21 publications
25
199
5
50
Order By: Relevance
“…These values, however, are slightly lower than those found for basketball players during one week with no competitive matches -3334±256 A.U. 1 . Such difference may be explained by the methodology used in the study by Manzi et al 1 , which used the total time of the session, including the resting period between the activities.…”
Section: Discussioncontrasting
confidence: 60%
See 4 more Smart Citations
“…These values, however, are slightly lower than those found for basketball players during one week with no competitive matches -3334±256 A.U. 1 . Such difference may be explained by the methodology used in the study by Manzi et al 1 , which used the total time of the session, including the resting period between the activities.…”
Section: Discussioncontrasting
confidence: 60%
“…1 . Such difference may be explained by the methodology used in the study by Manzi et al 1 , which used the total time of the session, including the resting period between the activities. Regarding the CP, we observed that our values are similar to those reported by Manzi et al 1 in two competitive weeks of basketball, with TL of 2928±303 and 2791±239 A.U.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations